Fabrication of Multi-Purpose Operation Machine - Shaik Khasim sharif; K.Bhanu Chandu; V.Sasidhar Reddy; P.Syam Sundara Rao; B.Susmitha (International Journal of Engineering and Management Research, 2023)
This paper presents about fabrication of multi-purpose operation machine for an industry. Different types of mechanical industries are producing useful goods and services at low cost and maximum efficiency. In order to produce these useful products many mechanical operations like drilling, cutting, grinding, milling, sawing, riveting, etc. are done on different components. Even though mechanical works are modernized but still we are using separate machines to do all mechanical operations. It will result in time consumption, more power usage, more space required and maintenance. This paper deals with reducing of all above problems by fabricating a “MULTI-PURPOSE OPERATION MACHINE”. This machine is designed for the purpose of multi operations i.e. drilling, cutting and grinding of a thin metals as well as wooden blocks. And can perfume multi operations at the same time with required electricity as it is pedaled. This machine is based on the mechanism of power transmission through bevel gears, chain drives. This multi operation machine is used in small scale industries and domestic operations.